Empowerment of Kelingan Hamlet Home Tofu Industry through Improving Production Quality and Utilizing Digital Technology - Febriayu, Lelita; Arif, Atika; Amin, Muhammad Rais; Gymnastiar, Wahyu; Syafina, Laylan (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This study examines efforts to improve the quality and production of tofu in the home industry, as well as the use of technology for marketing of MSMEs. This study uses field observation, interview, and literature analysis methods to identify challenges and solutions in small-scale tofu production. The results of the study indicate that improving water quality, standardizing production processes, and utilizing digital technology for marketing can significantly improve product quality and market reach. In conclusion, the integration of appropriate technology and digital marketing strategies can be a catalyst for the development of the home tofu industry and MSMEs in general.